Identification of distinct loci for de novo DNA methylation by DNMT3A and DNMT3B during mammalian development - Masaki Yagi (Nature Portfolio, 2020)
De novo DNA methylation is carried out by DNMT3A and DNMT3B, but the distinct functions of these two enzymes is poorly understood. Here the authors present a comprehensive, genome-wide identification of target sites for de novo DNA methylation by the DNMT3A and DNMT3B in mouse ES cells and embryos, identifying unique de novo DNA methylation target sites for both DNMT3 enzymes.